KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK SOSIS AYAM DENGAN PROPORSI KACANG MERAH KUKUS DAN MINYAK KELAPA SAWIT - Prijambodo, Octavia Miraclania; Trsinawati, Chatarina Yayuk; Sutedja, Anita Maya (Widya Mandala Surabaya Catholic University, 2014)
Chicken sausage processing did by reducing fat (palm oil) and substituted with fat replacer, fat mimetics type such as steamed red bean. The research aimed to determine the effect of the proportion of steamed red beans and palm oil to physicochemical and sensory characteristics of chicken sausages. The research design used a randomized block design, single factor. The factor is proportion of steamed red bean and palm oil which consists of six levels 0%:100%, 20%:80%, 40%:60%, 60%:40%, 80%:20% and 100%:0% with four times repetition. Increased proportion of steamed red bean and palm oil will increased the moisture content, hardness, gumminess and chewiness, but decreased juiciness, springiness and sensory properties of chicken sausage. The research resulted that proportion of steamed red bean and palm oil do not affect the cohesiveness and adhesiveness of chicken sausages. The proportion of steamed red bean and palm oil which acceptabled was 40%:60.